The impact of a 6-week strength training program on physiological and hematological metrics in elite Ethiopian middle- to long-distance runners - Angasu, N. W.; Tola, Z. B.; Taddese, A. (Journal of Human Sport & Exercise, 2025)
This study examined the effects of a 6-week strength training (StT) program on elite middle- to long-distance runners (1,500m-10,000m). While strength training is recognized for improving athletic performance, its specific impact on physiological and haematological parameters in Ethiopia remains unclear. Twenty-one elite athletes underwent pre- and post-training assessments, measuring resting heart rate (RHR), maximal oxygen consumption (VO2max), 5000m race time, 400m speed, and haematological markers, including red blood cell (RBC) count, white blood cell (WBC) count, haemoglobin (Hb), and haematocrit (Hct). Results showed that 5000m performance significantly improved (p < .001), demonstrating the positive effect of StT on endurance. Regression and ANOVA analyses revealed strong predictive relationships for VO2max (R² = 0.304, p = .010), 5000m time (R² = 0.719, p < .001), 400m speed (R² = 0.784, p < .001), and Hct levels (R² = 0.894, p < .001). No significant changes were found in RBC, WBC, or Hb levels. These findings suggest strength training enhances endurance performance without significantly affecting haematological parameters, emphasizing the need for further research on long-term haematological adaptations. This research contributes valuable insights into the effectiveness of strength training interventions for enhancing athletic performance.